2021
DOI: 10.1007/s12032-021-01566-y
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed PLIN3 frequently occurs in prostate cancer, promoting docetaxel resistance via intensified autophagy, an event reversed by chloroquine

Abstract: Lipid metabolism reprogramming is one of the adaptive events that drive tumor development and survival, and may account for resistance to chemotherapeutic drugs. Perilipins are structural proteins associated with lipophagy and lipid droplet integrity, and their overexpression is associated with tumor aggressiveness. Here, we sought to explore the role of lipid droplet-related protein perilipin-3 (PLIN3) in prostate cancer (PCa) chemotherapy. We investigated the role of PLIN3 suppression in docetaxel cytotoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…PLIN3, as a surface protein of LDs, can regulate LD biosynthesis and degradation [ 42 ]; PLIN3 associates with LDs in a manner that is responsive to the status of neutral lipid synthesis and storage in the cell [ 21 ]. At the same time, PLIN3 plays an important role in cell viability and autophagy, which can lead to drug resistance to treatment [ 43 ]. Kaplan–Meier curves revealed that elevated PLIN3 predicted poor DFS and OS in clear cell renal cell carcinoma [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLIN3, as a surface protein of LDs, can regulate LD biosynthesis and degradation [ 42 ]; PLIN3 associates with LDs in a manner that is responsive to the status of neutral lipid synthesis and storage in the cell [ 21 ]. At the same time, PLIN3 plays an important role in cell viability and autophagy, which can lead to drug resistance to treatment [ 43 ]. Kaplan–Meier curves revealed that elevated PLIN3 predicted poor DFS and OS in clear cell renal cell carcinoma [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan–Meier curves revealed that elevated PLIN3 predicted poor DFS and OS in clear cell renal cell carcinoma [ 22 ]. In prostate cancer, PLIN3 overexpression promotes tumor progression [ 43 ]. Similar to previous studies, we demonstrated that PLIN3 was upregulated and predicted a poor prognosis in OSCC, suggesting that PLIN3 accumulated in cells to serve as a conservative oncogene to promote cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Patient 229 presented a heterozygous loss of the TICAM1 (TIR domain-containing adaptor molecule 1) and PLIN3 (lipid droplet-related protein perilipin-3) genes. Perilipins are structural proteins associated with lipophagy and lipid droplet integrity, and their overexpression is associated with tumor aggressiveness, while TICAM1 participates in immune and inflammation responses to malignant cells [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid metabolism was an important driving force for tumor occurrence and development, and it was also the reason why PCa was resistant to chemotherapy drugs. 26 It showed that AEGs were involved in lipid metabolism to achieve the regulation of resistance to PCa.…”
Section: Discussionmentioning
confidence: 99%